FAKTOR MAHALNYA HARGA SAYURAN DI KABUPATEN AGAM DAN IMPLIKASINYA TERHADAP PENDAPATAN PETANI - Finni Jum’atul Ummy; Rantika Nurul Azani; Shelvi Nessya Adlin; Yestin Aprilia; Zul Wahid Novendra; Zuwardi (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2026)
As an agricultural country, agriculture is one of the most important industries in the world. In Indonesia, this is reflected in the role of the agricultural sector in providing land. Foreign exchange contribution through labor, food supply, exports, etc. The development of the times has led to an increase in the direction of the agricultural sector. Even industrial areas where companies were established or residential areas were expanded. In writing this scientific work the author uses a descriptive analytical method whose approach is qualitative and quantitative. Land is a limited natural resource. Land is important because its existence is necessary for human survival in carrying out their activities. Agricultural land is a production factor that plays a very important role in agriculture compared to other production factors. Without land there is no agriculture. Land is the place where agriculture can operate. There are several factors that cause the price of vegetables in Agam Regency to be high, including land conversion. The impact of land conversion is to cause changes in the economic activities of land converters or farmers. This change is very significant. The economic activities carried out were initially related to agriculture.